2001
DOI: 10.1136/bmj.323.7307.253
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relation of inhaled fluticasone propionate in adolescents and adults with asthma: meta-analysis Commentary: Dosage needs systematic and critical

Abstract: Objective To examine the dose-response relation of inhaled fluticasone propionate in adolescents and adults with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
116
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 30 publications
11
116
2
5
Order By: Relevance
“…A recent meta-analysis indicated that maximal symptom and lung function improvements were found at low-to-medium doses (table 1) of inhaled fluticasone propionate. 10 Similar observations were made in a 24-week study comparing increasing doses of inhaled fluticasone propionate and beclomethasone dipropionate. 11 A study employing bronchial biopsies also failed to confirm enhanced in vivo anti-inflammatory benefits with very high doses of fluticasone propionate.…”
Section: Introductionsupporting
confidence: 61%
“…A recent meta-analysis indicated that maximal symptom and lung function improvements were found at low-to-medium doses (table 1) of inhaled fluticasone propionate. 10 Similar observations were made in a 24-week study comparing increasing doses of inhaled fluticasone propionate and beclomethasone dipropionate. 11 A study employing bronchial biopsies also failed to confirm enhanced in vivo anti-inflammatory benefits with very high doses of fluticasone propionate.…”
Section: Introductionsupporting
confidence: 61%
“…However, these conventional parameters of asthma control may be more downstream from the underlying inflammatory process. The doseresponse curve with ICS for these conventional outcomes is rather shallow, as shown in a meta-analysis with fluticasone propionate (FP) [3], where a plateau effect on lung function was achieved above 100 m g twice daily, suggesting that other surrogate markers of inflammation may be more sensitive. Airway hyperresponsiveness is a noninvasive surrogate marker of airway inflammation and is a sensitive method of assessing the short-and long-term response to ICS [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has become increasingly clear that they are clinically very effective from the lowest available doses upwards. Regarding their effects on the airways, the dose-response curve for these commercially-available doses is flat [1]. The effect on structural airway changes, the so-called airway remodelling, is less clear.…”
mentioning
confidence: 99%